The cultural dimension of town twinning on the example of Częstochowa and Pforzheim - Kaczmarek, Hanna; Ławnikowska-Koper, Joanna (Acta Universitatis Lodziensis. Folia Germanica, 2017)
Town twinning in Europe is a unique example of civic activity for the fostering of links between nations. Since the 1950s, the experience gained by the French, German and British communities has contributed to the rapid development of this form of international cooperation also in Poland, after its accession to the European Union (2004).The article shows, on the example of cooperation between the cities of Częstochowa and Pforzheim, how valuable and inspiring are the cultural activities undertaken by the city dwellers regardless of their age and profession. This cooperation demonstrates that the shared experience of culture by partner communities, especially by Poles and Germans, builds a lasting foundation for the close neighbourly relations.